2014
DOI: 10.1080/10494820.2014.917107
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting reading anxiety for promoting English-language reading performance based on reading annotation behavior

Abstract: To reduce effectively the reading anxiety of learners while reading English articles, a C4.5 decision tree, a widely used data mining technique, was used to develop a personalized reading anxiety prediction model (PRAPM) based on individual learners' reading annotation behavior in a collaborative digital reading annotation system (CDRAS). In addition to forecasting immediately the reading anxiety levels of learners, the proposed PRAPM can be used to identify the key factors that cause reading anxiety based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Similar to Blyth (2014), we found that the instructor gained valuable insights regarding their students' understanding of the various Hispanic poems read and annotated via Hylighter. In contrast to previous work on the use of DATs in an L2 classroom context (e.g., Chen et al, 2016;Thoms, Sung, & Poole, 2017;Yu, 2014), this study noted that a majority of students' annotated comments were either literary or social in nature, with few focusing on linguistic issues (i.e., lexical or grammatical queries to fellow students).…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…Similar to Blyth (2014), we found that the instructor gained valuable insights regarding their students' understanding of the various Hispanic poems read and annotated via Hylighter. In contrast to previous work on the use of DATs in an L2 classroom context (e.g., Chen et al, 2016;Thoms, Sung, & Poole, 2017;Yu, 2014), this study noted that a majority of students' annotated comments were either literary or social in nature, with few focusing on linguistic issues (i.e., lexical or grammatical queries to fellow students).…”
contrasting
confidence: 92%
“…Research on DATs has thus far primarily been carried out in first language (L1) contexts (e.g., Gao, 2013;Kiili, Laurinen, Marttunen, & Leu, 2012;Lu & Deng, 2013;Mendenhall & Johnson, 2010;Yang, Yu, & Sun, 2013;Zarzour & Sellami, 2017), where learners read literary texts written in their L1 and provide annotated comments on them using their L1. In L2 contexts, initial studies have mostly investigated the impact of DATs on English as a Foreign Language (EFL) students, specifically targeting student perceptions (Lo, Yeh, & Sung, 2013;Nor, Azman, & Hamat, 2013), the impact of DATs on reading comprehension scores (Chang & Hsu, 2011;Yeh, Hung, & Chiang, 2017;Yu, 2014), and/or how different uses of DATs by students impact reading skills and approaches (Chen, Wang, Chen, & Wu, 2016;Tseng, Yeh, & Yang, 2015;Yeh, Hung, & Chiang, 2017;Yu, 2014).…”
Section: Dat Research In L2 Contextsmentioning
confidence: 99%
“…The most common features were related to communication: CMC such as text chat and online forums ( Arnold, 2007 ), student–student interactions such as peer feedback ( Bailey and Cassidy, 2019 ), and teacher-student interaction such as portfolio assessment ( Nosratinia and Abdi, 2017 ). Some interventions included both student–student and teacher-student interactions ( Liao and Wang, 2015 ; Chen et al, 2016 ; Tang, 2016 ), and some had both CMC and student–student/teacher-student communication (e.g., Ku and Chen, 2015 ). Our review further found learner-internal features of FLAR interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the influence of computer-assisted language learning on reading achievement was determined (Khezrlou, Ellis, & Sadeghi, 2017). In addition, few researchers considered the association between psychological variables and reading comprehension performance including anxiety (Chen et al, 2016;Tsai & Lee, 2018), motivation (Galgao, 2016), self-efficacy beliefs (Shehzad et al, 2019), multiple intelligence (Rostami Abu Saeedi & Jafarigohar, 2019;Zahedi & Moghaddam, 2016), critical thinking (Fahim & Barjesteh, 2018), and reading enjoyment (Tavsancil, Yildirim, & Bilican Demir, 2019). Despite the keen interest of researchers regarding the association of psychological variables with EFL reading comprehension performance, there is paucity of research involving a well-researched psychological variable in other fields, i.e., boredom.…”
Section: Reading Comprehension Performancementioning
confidence: 99%